Strategi Kepala Madrasah Dalam Mengembangkan Profesional Guru Pendidikan Agama Islam Berbasis Artificial Intelligence - Yunita, Yunita; Janah, Miftahul; Suwadi, Suwadi (PT. Student RIhlah Indonesia, 2025)
This study aims to describe the strategy of Madrasah head in developing professionalism of PAI teachers based on Artificial Intelligence (AI). This research is a type of library research using secondary sources in the form of books and scientific journals and data collection methods of documentation studies and using content analysis data analysis methods. The results showed that the development of technology is currently very rapid, especially AI artificial intelligence has had a major impact on the education sector, especially in Islamic religious education, IA technology makes it easier for educators to deliver teaching materials and interesting methods, so as to make students not feel bored and bored, can improve the quality of the teaching and learning process that is more active and innovative, measure student understanding, and accelerate student understanding of Islamic religious education. Through AI technology such as visual mentors, Voice Assistants such as Google Assistant, Siri, and Cortana and Presentation Translator.